ZnO Nanorod Array Modified PVDF Membrane with Superhydrophobic Surface for Vacuum Membrane Distillation Application - Wang, Manxiang; Liu, Guicheng; Yu, Hyunjin; Lee, Sang-Hyup; Wang, Lei; Zheng, Jianzhong; Wang, Tao; Yun, Yanbin; Lee, Joong Kee (American Chemical Society, 2018)
The vacuum membrane distillation (VMD) is a promising technology for lots of applications. To solve the membrane fouling and wetting problems, in this paper, a novel ZnO nanorods 1H,1H,2H,2H-perfluorodecyl-triethoxysilane (PDTS) modified poly(vinylidene fluoride) (PVDF) membrane with a micro/nanoscale hierarchical structure and a superhydrophobic surface has been prepared and applied to the VMD process for distilling highly salty water, for the first time. Among these, a pyrolysis adhesion method is created to obtain the ZnO seeds and fasten them on the PVDF substrate firmly. The novel modified membrane shows a stable superhydrophobic surface with a water contact angle of 152, easy cleaning property, excellent thermal and mechanical stability, because of the Cassie's state caused by pocketing much air in the hydrophobized ZnO nanorods, the low surface energy of PDTS coating, and the strong adhesion between ZnO nanorods and PVDF membrane, which has built an ideal structure for VIVID application. After 8 h VMD of 200 g L-1 NaCl solution, compared to the virgin PVDF membrane, the novel membrane shows a similar permeate flux but a much higher quality permeated liquid because of its unique antifouling and antiwetting caused by the several microns gap between the feed and the membrane. Due to its easy cleaning property, the novel membrane also exhibits an excellent reusability.
Keywords: ELECTROSPUN NANOFIBER MEMBRANES; TIO2 NANOCOMPOSITE; FIBER MEMBRANES; WATER; ENERGY; DESALINATION; ULTRAFILTRATION; PERMEABILITY; PERFORMANCE; FABRICATION